2013
DOI: 10.1176/appi.ps.201300015
|View full text |Cite
|
Sign up to set email alerts
|

Research and Services Partnerships: The Practice Research Network: A Successful Collaboration in Maryland

Abstract: The Practice Research Network (PRN) in Maryland is a Interventions and Practice Research Infrastructure Support Project supported by NIMH that extends the historically close collaborative relationship between the University of Maryland Department of Psychiatry and the State Mental Hygiene Administration. This project focuses on the relationship between University-based investigators and participants in the Public Mental Health System using the local mental health authorities which are known as Core Service Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Studies evaluating the effectiveness of recruitment practices are scarce (14,15). The suggestions below are based on published articles that detail successful strategies for participant recruitment (49), identify barriers to recruitment (9,11,12,15), and on a review of recruitment strategies (14). Close collaboration between researchers and clinics has been described as promising (11,15).…”
Section: Collaboration Between Clinics and Researchersmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating the effectiveness of recruitment practices are scarce (14,15). The suggestions below are based on published articles that detail successful strategies for participant recruitment (49), identify barriers to recruitment (9,11,12,15), and on a review of recruitment strategies (14). Close collaboration between researchers and clinics has been described as promising (11,15).…”
Section: Collaboration Between Clinics and Researchersmentioning
confidence: 99%
“…Emphasizing the importance of collaboration, Sundeen et al (49) reported on a model that may serve as an example. The model incorporated regular meetings between clinics and researchers as well as designated research liaisons at the clinics.…”
Section: Collaboration Between Clinics and Researchersmentioning
confidence: 99%
“…Shared awareness at the local, regional, and state level led to a joint effort among behavioral health providers, key personnel from the Connecticut Department of Mental Health and Addiction Services 3 (DMHAS), the Connecticut Mental Health Center (CMHC), state legislators, and the Yale University Department of Psychiatry to request funds from the State General Assembly to implement systemic strategies that would ultimately reduce short-term, ineffective alternatives to care, and increase the availability of long-term, responsible, and cost-effective solutions. Examples of this type of statewide collaboration have proven successful (Sundeen, Goldman, Nieberding, Piez, & Buchanan, 2013; Wells et al, 2006) in their ability to pool resources and achieve a common goal.…”
Section: A Culturally Informed System Of Carementioning
confidence: 99%
“…All this innovation is being spurred and supported by the development of centers for practice innovation in states such as Maryland and New York [24]. This work is being informed by greater recognition of the assets and resources that communities can provide the treatment and support of the mentally ill through authentic engagement with community-based leaders and organizations, as exemplified by the work of Ken Wells and his colleagues at UCLA [25].…”
Section: The Current State Of Mental Health Reformmentioning
confidence: 99%